A novel plithogenic MCDM framework for credit evaluation of bidding and tendering in construction projects with contradictions - Maohua Yang; Jiajia Yu; Yuhe Wang (Neutrosophic Sets and Systems)
This paper introduces a novel approach to decision-making by integrating Plithogenic modeling methodology with multi-criteria decision-making (MCDM) techniques. Traditional Plithogenic decisionmaking frameworks primarily rely on degrees of appurtenance as their foundation. However, this study presents a new paradigm that leverages degrees of contradiction to rank alternatives, offering a unique and innovative perspective compared to conventional methods. The research employs the PROMETHEE method to evaluate and rank alternatives, with the assessment carried out by four experienced experts using Plithogenic numbers. A total of ten criteria and five alternatives were analyzed in this study. The findings highlight that the Financial Stability criterion holds the highest importance, while the Risk Management Strategy criterion is weighted the lowest. This demonstrates the capability of the proposed method to address complex decision-making scenarios in the construction bidding and tendering context.